Quality, Equity, Inclusion and Lifelong Learning in Pre-service Teacher Education - Wisuit Sunthonkanokpong; Elizabeth Murphy (My University, 2019)
Abstract Sustainable Development Goal 4 (SDG 4) focuses on ensuring inclusive and equitable, quality education and lifelong learning opportunities for all. One of the three means of implementation of SDG 4 targets is SDG 4c which calls on countries and donors to significantly increase the supply of qualified teachers in developing and underdeveloped countries. This emphasis on the supply of teachers is in recognition of the fact that the quality of education ultimately depends on teachers. In general, there is widespread agreement that teacher education has an important role to play in the achievement of the SDG 4 targets. However, there has been limited attention in the literature to SDG 4 in a context of teacher education. This paper aims to contribute to the literature on SDG 4 and teacher education. The paper first presents a conceptual framework pertaining to quality, equity, inclusion, and lifelong learning. Next, the framework is applied to the case of Thailand to identify examples of progress the country is making in support of realization of SDG 4 in teacher education. The framework with the four concepts can be applied by researchers to identify examples of progress on SDG 4 in teacher education in other countries and contexts.
Keywords: Equity; Global Educational Policies and Reforms